Newly Identified Pathogens Associated with Periodontitis: A Systematic Review. (September 2014) - Pérez-Chaparro, P.J.; Gonçalves, C.; Figueiredo, L.C.; Faveri, M.; Lobão, E.; Tamashiro, N.; Duarte, P.; Feres, M.
There is substantial evidence supporting the role of certain oral bacteria species in the onset and progression of periodontitis. Nevertheless, results of independent-culture diagnostic methods introduced about a decade ago have pointed to the existence of new periodontal pathogens. However, the data of these studies have not been evaluated together, which may generate some misunderstanding on the actual role of these microorganisms in the etiology of periodontitis. The aim of this systematic review was to determine the current weight of evidence for newly identified periodontal pathogens based on the results of "association" studies. This review was conducted and reported in accordance with the PRISMA statement. The MEDLINE, EMBASE, and Cochrane databases were searched up to September 2013 for studies (1) comparing microbial data of subgingival plaque samples collected from subjects with periodontitis and periodontal health and (2) evaluating at least 1 microorganism other than the already-known periodontal pathogens. From 1, 450 papers identified, 41 studies were eligible. The data were extracted and registered in predefined piloted forms. The results suggested that there is moderate evidence in the literature to support the association of 17 species or phylotypes from the phyla Bacteroidetes, Candidatus Saccharibacteria, Firmicutes, Proteobacteria, Spirochaetes, and Synergistetes . The phylum Candidatus Saccharibacteria and the Archaea domain also seem to have an association with disease. These data point out the importance of previously unidentified species in the etiology of periodontitis and might guide future investigations on the actual role of these suspected new pathogens in the onset and progression of this infection.